Parametric study of adhesive joints by using the probabilistic finite element approach - Chen, Weixu (2006)
The thermal stresses in adhesive joints due to the large difference in thermal expansion between dissimilar materials presenting in adhesive electronic packages is the source of a major problem to be solved in order to achieve improved reliability. However, because of the shortage of the facilitated experiment data for the thermal mechanical characterizations of adhesive joint and in order to fully investigate this issue, a finite element based parametric study on an adhesive joint is implemented in this paper by using the probabilistic method. It combines the Monte Carlo simulation (MCS) and response surface method (RSM). The Monte Carlo simulation has been carried out to analysis reliability and parametric sensitivity on adhesive joint. The response surface approximate functions between the output shear stress values and the significant joint design parameters derived from above Monte Carlo simulation and sensitivity analysis are fitted to observe the interactions between each parameter. Full thermal mechanical probabilistic finite element analysis is made by using the commercial engineering computer package ANSYS/PDS.